Pengembangan Alat Permainan My Costume untuk Menstimulasi Kecerdasan Visual-Spasial pada Anak Usia Dini Autis - Tejaningrum, Dhiarti (INKLUSI, 2014)
Game is one of learning tools in early education for any children. My Costume is a game to stimule visual-spacial intellegence of children with autism. This tool is constructed from Research and Development (R&D) study which utilizes the theories of M. Alessi Stephen R. Stanley Trollip (development theory) and Howard Gardner (early education curricullum for children with autism). The stages of the research as follows: analysis, design and development. The development is conducted after obtaining validation from material/content expert, media specialist and limited experimental research. The research shows that the product of My Costume in general is appropriate to stimulate visual-spacial intellegence of children with autism in early education context. This is based on the of alpha tests from content expert is 4,6 (very good), alpha test from media specialist is 4,2 (good) whereas beta test obtains 4,27 (very good) and the final result is 4,06 (good). Pre-test visual-spacial intellegence assesment score is 2,18 (poor) and post-test is 3,45 (good). Nevertheless, we can conclude that the product of My Costume is very appopriate to be a visual-spacial learning tool for children with autism.